Activation of nano-Ca2MnO4 for electrochemical lithium intercalation. Issue 1805 (7th August 2015) - Surace, Yuri; Simões, Mário; Karvonen, Lassi; Battaglia, Corsin; Pokrant, Simone; Weidenkaff, Anke
ABSTRACT: Ca2 MnO4 nanoparticles were prepared by the Pechini method and acid treated to extract Ca 2+ ions. Structural, morphological and spectroscopic analyses by XRD, SEM/EDX, TEM/EDS and Raman revealed the formation of an amorphous outer layer at the particles surface with a preserved inner crystalline bulk. Thanks to the outer layer, which is electrochemically active, the acid-treated compounds showed capacity up to 150 Ah/kg. The crystalline bulk improved cycling stability, allowing reaching capacity retention up to 70% after 30 cycles.